How Political Careers affect Prime-Ministerial Performance: Evidence from Central and Eastern Europe. (September 2021) - Grotz, Florian; Müller-Rommel, Ferdinand; Berz, Jan; Kroeber, Corinna; Kukec, Marko
Even though Prime Ministers (PMs) are the central actors in parliamentary democracies, little comparative research explores what makes them perform successfully in office. This article investigates how the political careers of PMs affect their performance. For this purpose, we make use of a unique expert survey covering 131 cabinets in 11 Central and Eastern European countries between 1990 and 2018. Performance is defined as a two-dimensional set of tasks PMs ought to fulfill: first, managing the cabinet and directing domestic affairs as tasks delegated to their office, second, ensuring support of parliament and their own party, who constitute the direct principals. The findings indicate that a simple political insider career is not sufficient to enhance prime-ministerial performance. Rather, PMs who served as party leaders have the best preconditions to succeed in office.